PENILAIAN AKTIVA TETAP PADA CV. TIGA BERSAUDARA DI TENGGARONG - -, Anita Rahayu (EKONOMIA, 2015)
The problem in this study whether the valuation of fixed assets in the financial statements of the CV. Three Brothers is in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) Chapter 15 on Fixed Assets while the purpose of this study to determine and analyze the application of the theory SAK ETAP Stay on valuation of fixed assets in the financial statements of the CV. Three Brothers.Basic financial accounting theory used in this study, while the hypothesis of Fixed Assets Assessment in Three Brothers CV financial statements not in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) Chapter 15 on Fixed AssetsTool analysis and discussion that has been done before, it can be concluded that the hypothesis is accepted because it turns out assessment of Fixed Assets in the financial statements CV. Three Brothers is not in accordance with Financial Accounting Standards Entities Without Public Policy (SAK ETAP) About Assets and result in the profit and loss for the following reasons:1 Fixed assets held and used in operations by CV. Three Brothers acquired cash and credit treatment is not fully in accordance with Financial Accounting Standards Entities Without Public Policy (SAK ETAP) on Fixed Assets.2 Given these differences is evident that as the cost of loading dock equipment so that the company does not perform adequate supervision and control of the assets it has. Thus the hypothesis is accepted